Study on complex flow law near polymer flooding wellbores and adaptability evaluation of shaped charges. Issue 5 (2nd September 2016) - Wei, Jianguang; Ren, Xidong; Shao, Hongyan; Ma, Yuanyuan; Liu, Xuemei; Lin, Xuesong
Abstract: The flow law near polymer flooding wellbores under the condition of perforation is very complex and there are many types of shaped charges. In this study, a non-Darcy flow model near polymer flooding wellbores was given, and a flow experiment was carried out to measure the resistance coefficient, residual resistance coefficient, and flow viscosity of the polymer solution in porous media under the conditions of different permeability and different polymer molecular weight. According to the results of numerical simulation, this paper calculated the flow efficiency of different types of shaped charges and evaluated the adaptability of different charges under polymer flooding condition. The results of this study have an important significance for guiding the optimization of shaped charges and the optimization design of perforating parameters.